Product of derivations on triangular banach algebras - Mohammad Hossein Sattari; Hamid Shafieasl (Journal of Hyperstructures, 2017)
In this paper, we give a necessary and sufficient condition for the product of two derivations on the triangular Banach algebra to be a derivation. We also study the case where the product of derivations is commutative.